A genome-wide screen reveals microRNAs in peripheral sensory neurons driving painful diabetic neuropathy - Bali, Kiran Kumar; Gandla, Jagadeesh; Rangel, Daniel Rojas; Castaldi, Laura; Mouritzen, Peter; Agarwal, Nitin; Schmelz, Martin; Heppenstall, Paul; Kuner, Rohini (Pain, 2021)
Diabetes is a leading cause of peripheral neuropathy (diabetic peripheral neuropathy, DPN), and uncontrolled long-lasting hyperglycemia leads to severe complications. A major proportion of diabetics develop excruciating pain with a variable course. Mechanisms leading to painful DPN are not completely understood and treatment options limited. We hypothesized that epigenetic modulation at the level of microRNA (miRNA) expression triggered by metabolic imbalance and nerve damage regulates the course of pain development. We used clinically relevant preclinical models, genome-wide screening, in silico analyses, cellular assays, miRNA fluorescent in situ hybridization, in vivo molecular manipulations, and behavioral analyses in the current study. We identified miRNAs and their targets that critically impact on nociceptive hypersensitivity in painful DPN. Our analyses identify miR-33 and miR-380 expressed in nociceptive neurons as critical denominators of diabetic pain and miR-124-1 as a mediator of physiological nociception. Our comprehensive analyses on the putative mRNA targets for miR-33 or miR-124-1 identified a set of mRNAs that are regulated after miR-33 or miR-124-1 overexpression in dorsal root ganglia in vivo. Our results shed light on the regulation of DPN pathophysiology and implicate specific miRNAs as novel therapeutic targets for treating painful DPN.